UANG DAN BUNGA DALAM PERSPEKTIF ISLAM - Baso R; Irwan Misbah; Rahmawati Muin; Sumarni S (Jurnal Akuntansi dan Keuangan, 2024)
Abstract This article aims to analyze the concept of money from an Islamic perspective, viewing money as a medium of exchange with a social function to support societal welfare rather than as a commodity that generates profit without productive activities. The analytical method examines Islamic principles of justice, honesty, and balance concerning the use of money, as well as the prohibition of interest (riba). The findings reveal that Islam rejects the interest-based system (riba) due to its potential to create social inequality and exploitation. As an alternative, the Islamic financial system emphasizes profit-sharing financing models, such as mudharabah and musharakah, which are fairer and prioritize the welfare of all parties involved. This concept is deemed relevant to achieving economic stability and equitable wealth distribution while fostering an ethical and sustainable economic system in the modern era. Keywords: Money in Islam, Social function of money, Prohibition of riba